Exploration of Acid-Tolerant Bacteria for Cellulose Production from Fruit Waste - Arifin, Auliyya Intan Mellaniy; Purwani, Kristanti Indah; Prasetyo, Endry Nugroho (Jurnal Biologi Tropis, 2025)
Bacterial cellulose is a natural biomaterial synthesized by certain bacterial species by producing protofibril threads that bind together to form strands of cellulose fibers or membranes. Bacterial cellulose has been widely used in various industrial fields, including biomedical such as wound dressings, the textile industry as a raw material for clothing, and the food industry for the manufacture of nata de coco. To support this industrial application, it is necessary to characterization of bacterial cellulose to increase the efficiency and quality of the production process. Therefore, this study aims to characterize bacterial cellulose produced by acid-fast bacteria isolated from fruit waste. This research involved the isolation, purification and characterization of cellulose producing bacteria. The result showed that acid-tolerant bacteria that were successfully isolated were 23. Purification and screening of bacteria that have the potential to produce cellulose obtained 6 isolates, namely SB 6, SB 13, SB 19, SB 20, SB 21, and SB 23. Macroscopic observation found that all bacteria have a circular colony, entire colony edge, shiny colony surface, convex elevation shape, while the colony color is different, SB 6 is yellowish cream, SB 13, 19, 23 cream, SB 20 orangeish cream, and SB 21 white. Macroscopic identification found that all isolates have Gram-negative types, and red cell color, for SB 6 cell shape is round and SB 13, 19, 20, 21, 23 bacilli (rods). The results of biochemical tests of cellulose-producing acid-resistant bacteria are all positive in the catalase test, Simmons Citrate test and carbohydrate fermentation test. The Indole test and Voges Proskauer test obtained negative test results on all isolates. The starch hydrolysis test was only positive on SB 21. The gelatin hydrolysis test was positive on isolates SB 6, 20, 21, 23, negative on isolates SB 13 and SB 19. The motility test for SB 6, 13, 19, 21 was positive, for SB 23 it was negative. The Methyl Red test was positive on isolates SB 6, 19, 20, 23, negative on isolates SB 13 and SB 21.